Tail Flick Modification of Orexin-A Induced Changes of Electrophysiological Parameters in The Rostral Ventromedial Medulla - Azhdari-Zarmehri, Hassan (Royan Institute, 2014)
OBJECTIVE: It is well known that intracerebroventricular (ICV) and supraspinal injections of orexin-A elicit analgesia, but the mechanism(s) of action remains unidentified. This study aims to characterize the effect of orexin-A on rostral ventromedial medulla (RVM) neurons which are involved in the descending nociception modulating pathway. MATERIALS AND METHODS: In this experimental study, we injected orexin-A or vehicle di- rectly into rats’ ICV while the tail flick (TF) latencies were measured and the on- and off-cell firing activities were monitored for more than 60 minutes. RESULTS: In response to noxious stimuli on the tail, we observed increased firing rate of on-cells and a decreased association with the firing rate of off-cells and in neutral cells the firing rate was unchanged just prior to tail flicking. ICV injection of orexin-A decreased the spontaneous firing rate of on-cells (the type of RVM neurons believed to have facilitatory action on nociception). Furthermore, orexin-A increased firing rate of off-cells (the type of RVM neurons believed to have an inhibitory action on nocicep- tion). Orexin-A reduced the TF-related responses of on-cells and TF-related pause duration of off-cells. CONCLUSION: These results have shown that the analgesic effect produced by orexin-A may be induced by brainstem neurons. It is suggested that the orexinergic system from the hypothalamus to the RVM may have a potential role in modulation of nociceptive transmission.